"Galileu Galilei: Carta à Senhora Cristina de Lorena, Grã-Duquesa de Toscana." - Brollo, Ana Paula (2006)
This dissertation has as subject the relation of Copernicus system with the Bible; a crucial question that may be analyzed in Galileo s Letter to Cristine of Lorene, wrote in 1615, in which this subject is treated by the celebrated Florentine. At first, some observations of Galileo are considered (solar spots, phases of Venus and Jupiter satellites) which gave credit to the thesis of Nicolaus Copernicus, who placed Sun in the center of Universe and made Earth to turn around itself and around the Sun. This thesis was introduced more than one half century before, but without proofs to support it. The observacional discoveries of Galileo provided support for the copernican system, being argued the character of this support: a rigorous proof (necessary demonstration) or endorcement of an hypothesis saving the phenomena . We endeavor to analyze the Letter of Galileo to Cristine of Lorene, stressing the strategies used by Galileo to show the agreement of the copernican system with the Bible; stressing also as Galileo conceives the study of the book of Nature and the interpretation of the Bible. For Galileo, Nature as much as Sacred Scripture are works of God; they are, therefore, two books without error and cannot contradict one another; however, Nature and Scripture are two books written in different languages, with different purposes, not being able to be read in the same way